1986
DOI: 10.1093/ajcn/43.3.406
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone and carrier protein interrelationships in children recovering from kwashiorkor

Abstract: We have studied 15 infants with severe protein energy malnutrition (PEM) as a model of nutritional nonthyroidal illness. Changes in circulating thyroid hormones, binding proteins, and their interrelationships were assessed before and during recovery. Serum concentrations of total thyroxine and triiodothyronine and of thyroxine-binding proteins were extremely reduced, and increased progressively during 3 wk of refeeding. The T4:TBG molar ratio was initially 0.180 +/- 0.020, and increased progressively, parallel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…On the contrary, subnormal RBP values were recorded in 11 of 32 (34%) patients and subnormal TTR values in only 5 out of 32 (16%). The mean values of RBP (43.3 ± 6.7 pg/mL) and of TTR (24.2 ± 4.4 mg/dL) were close to the lower limit accepted for normal subjects (20,21). The linear regression analysis revealed that RBP and retinol/RBP ratio, but not TTR, and TSH levels were closely correlated (r = -0.514; p < 0.0026 and r = -0.6559; p < 0.0001, respectively).…”
Section: Resultssupporting
confidence: 74%
“…On the contrary, subnormal RBP values were recorded in 11 of 32 (34%) patients and subnormal TTR values in only 5 out of 32 (16%). The mean values of RBP (43.3 ± 6.7 pg/mL) and of TTR (24.2 ± 4.4 mg/dL) were close to the lower limit accepted for normal subjects (20,21). The linear regression analysis revealed that RBP and retinol/RBP ratio, but not TTR, and TSH levels were closely correlated (r = -0.514; p < 0.0026 and r = -0.6559; p < 0.0001, respectively).…”
Section: Resultssupporting
confidence: 74%
“…Low levels of thyroid hormones binding proteins in malnutrition are thought to be due to decreased protein intake and their reduced hepatic biosynthesis (11). The rise in serum total T 3 and T 4 levels that occur on re-feeding can be largely accounted for by the increasing concentration of TBG, TBPA and albumin.…”
Section: Result8 and Discu8810nmentioning
confidence: 99%
“…In general, cortisol levels in children with severe malnutrition are similar to levels in children without malnutrition or are increased, which is likely related to stress and indicates that the hypothalamic-pituitary-adrenal axis is preserved in children with severe malnutrition and is probably not responsible for the development of hypoglycaemia 64,74,75 . Most studies have shown a reduction in thyroid function in children with severe malnutrition, but the clinical relevance of this remains unclear 76,77 . In addition, leptin concentrations are low in children with severe malnutrition, reflecting the extent of adipose tissue loss.…”
Section: Underlying Mechanismsmentioning
confidence: 99%